Knowledge And Attitude Towards Abnormally Excessive Sweating On The Hands (Palmar Hyperhidrosis) Among Malaysian Undergraduate Students (Journal of Pharmaceutical Negative Results, 2023)
Palmar hyperhidrosis is a medical condition in which a person's hands sweat excessively and uncontrollably. Even when the temperature is cool or when at rest, their hands will continue to sweat. Under certain circumstances or situations that make them anxious, frightened, angry, or even ashamed, their hands tend to sweat even more. Abnormal excessive sweating on the hands may occur without causes. This may be because the sweat glands in the hands appear to be overactive in palmar hyperhidrosis patients. It is proven that sweating uncontrollably can cause significant physical and mental discomfort towards affected individuals. There are generally two types of hyperhidrosis, primary and secondary. Primary hyperhidrosis may be localized such as on the hands, feet, and armpits and normally affects 2–3% of the population. However, only around 40% of patients reach out for medical assistance. There is no clear etiology for primary hyperhidrosis in most cases and appears to be genetic. Secondary hyperhidrosis on the other hand, is associated with other health issues and the excessive sweating may occur systemic. Society’s ignorance towards palmar hyperhidrosis has caused affected individuals to be wrongly stigmatized and thus impacted their overall wellbeing. Therefore, taking into consideration that the youth are the future of this nation, we had conducted this study amongst undergraduate students and have utmost faith that this study provided us an opportunity to better understand as well as increased the knowledge and attitude towards abnormal excessive sweating on the hands (palmar hyperhidrosis) amongst undergraduate students. Cross-sectional and convenience sampling method was used throughout the research whereby the respondents consisted of 312 undergraduate students; 98 Malays, 109 Chinese and 105 Indians from both medical and non-medical fields. The responses were collected through online platforms. The collected data was then analyzed using Statistical Package for Social Science (SPSS). Based on the data collected regarding comparison of the knowledge between medical and non-medical undergraduate students towards abnormally excessive sweating on the hands (palmar hyperhidrosis), questions 1,2,3,5,7,8 and 10 were statistically significant with p values less than 0.05 (p<0.05) whereas questions 4,6 and 9 showed no significance as their p values were greater than 0.05 (p >0.05). In addition to that, the comparison of attitudes between medical and non-medical undergraduate students towards abnormally excessive sweating on the hands (palmar hyperhidrosis) displayed that questions